Water Supply and Stormwater Management Benefits of Residential Rainwater Harvesting in U.S. Cities. (15th March 2013) - Steffen, Jennifer; Jensen, Mark; Pomeroy, Christine A.; Burian, Steven J.
Abstract: This article presents an analysis of the projected performance of urban residential rainwater harvesting systems in the United States (U.S.). The objectives are to quantify for 23 cities in seven climatic regions (1) water supply provided from rainwater harvested at a residential parcel and (2) stormwater runoff reduction from a residential drainage catchment. Water‐saving efficiency is determined using a water‐balance approach applied at a daily time step for a range of rainwater cistern sizes. The results show that performance is a function of cistern size and climatic pattern. A single rain barrel (190 l [50 gal]) installed at a residential parcel is able to provide approximately 50% water‐saving efficiency for the nonpotable indoor water demand scenario in cities of the East Coast, Southeast, Midwest, and Pacific Northwest, but <30% water‐saving efficiency in cities of the Mountain West, Southwest, and most of California. Stormwater management benefits are quantified using the U.S. Environmental Protection Agency Storm Water Management Model. The results indicate that rainwater harvesting can reduce stormwater runoff volume up to 20% in semiarid regions, and less in regions receiving greater rainfall amounts for a long‐term simulation. Overall, the results suggest that U.S. cities and individual residents can benefit from implementing rainwater harvesting as a stormwater control measure and as an alternative source of water.